De novo variants in CDK13 associated with syndromic ID/DD: Molecular and clinical delineation of 15 individuals and a further review. Issue 5 (14th April 2018) - van den Akker, W.M.R.; Brummelman, I.; Martis, L.M.; Timmermans, R.N.; Pfundt, R.; Kleefstra, T.; Willemsen, M.H.; Gerkes, E.H.; Herkert, J.C.; van Essen, A.J.; Rump, P.; Vansenne, F.; et al.
Abstract : De novo variants in the gene encoding cyclin‐dependent kinase 13 (CDK13) have been associated with congenital heart defects and intellectual disability (ID). Here, we present the clinical assessment of 15 individuals and report novel de novo missense variants within the kinase domain of CDK13. Furthermore, we describe 2 nonsense variants and a recurrent frame‐shift variant. We demonstrate the synthesis of 2 aberrant CDK13 transcripts in lymphoblastoid cells from an individual with a splice‐site variant. Clinical characteristics of the individuals include mild to severe ID, developmental delay, behavioral problems, (neonatal) hypotonia and a variety of facial dysmorphism. Congenital heart defects were present in 2 individuals of the current cohort, but in at least 42% of all known individuals. An overview of all published cases is provided and does not demonstrate an obvious genotype‐phenotype correlation, although 2 individuals harboring a stop codons at the end of the kinase domain might have a milder phenotype. Overall, there seems not to be a clinically recognizable facial appearance. The variability in the phenotypes impedes an à vue diagnosis of this syndrome and therefore genome‐wide or gene‐panel driven genetic testing is needed. Based on this overview, we provide suggestions for clinical work‐up and management of this recently described ID syndrome. Abstract : De novo CDK13 variants.